The roles of the independent actuary in the assessment of damages caused to persons by traffic accidents according to the Spanish legal framework - Gómez-Pérez-Cacho, Olga; Moreno-Ruiz, Rafael; Trigo-Martínez, Eduardo (My University, 2019)
The roles of the independent actuary in the assessment of damages caused to persons by traffic accidents according to the Spanish legal framework
Keywords: Accidentes de tráfico - Derecho; actuarial; valuation; professionalisim; traffic injury